Cognitive radio‐enabled Internet of Vehicles: a cooperative spectrum sensing and allocation for vehicular communication. Issue 4 (1st July 2018) - Eze, Joy; Zhang, Sijing; Liu, Enjie; Eze, Elias
Abstract : Internet of Things (IoTs) era is expected to empower all aspects of Intelligent Transportation System (ITS) to improve transport safety and reduce road accidents. US Federal Communication Commission (FCC) officially allocated 75 MHz spectrum in the 5.9 GHz band to support vehicular communication. The authors studied the application of cognitive radio (CR) technology to IoVs to increase the spectra opportunities for vehicular communication, especially when the allocated 75 MHz is not enough due to high demands because of the increasing number of connected vehicles as already foreseen in the near era of IoVs. They proposed a novel CR Assisted Vehicular NETwork (CRAVNET) framework which empowers CR enabled vehicles to make opportunistic usage of licensed spectrum on the highways. They also developed a novel cooperative three‐state spectrum sensing and allocation model which makes CR vehicular secondary units aware of additional spectrum resources opportunities on their current and future positions, and applies optimal sensing node allocation algorithm to guarantee timely acquisition of the available channels within a limited sensing time. The results of the theoretical analyses and simulation experiments have demonstrated that the proposed model can significantly improve the performance of a cooperative spectrum sensing, and provide vehicles with additional spectrum opportunities.